Death and Burial in Iron Age Israel, Aram, and Phoenicia - Nabulsi, Rachel (Gorgias Studies in the Ancient Near East, 2017)
Death and Burial uses archaeological and textual evidence to examine death and burial in Iron Age Israel and Aram. Despite dramatic differences in the religious systems of these peoples, this monograph demonstrates striking connections between their basic material and psychological frameworks for dealing with death.